Insulator surface condition monitoring system for leakage current analysis - Zainal Abidin, Nur Qamarina (2015)
There are several ageing factors that affect the long term performance of insulating material such as electrical stress, biological attack, and outdoor weathering contamination. Leakage Current (LC) is one of the key methods of measuring the insulator surface conditions which can cause tracking, erosion and flashover. Hence, an automated monitoring system is needed to reduce diagnostic time, rectify severity and ensure quality of insulator performance. This research presents the development of leakage current monitoring system to analyse insulator surface condition using Time-Frequency Distribution (TFD). To develop the system, a pre-information of the leakage current signal analysis is needed. Many previous researchers used Fast Fourier Transform (FFT) method for the analysis which gives spectral information; but it has some limitations in non-stationary signal, for example it does not provide temporal information. In this research, spectrogram is used to analyse the leakage current signals that consist of multi-frequency components and magnitude variations. From the Time-frequency representation (TFR) obtained using the time-frequency distribution, parameters of leakage current signal are calculated such as instantaneous of root mean square (RMS) current, fundamental RMS current, total harmonic distortion, total non-harmonic distortion, and total waveform distortion. The leakage current signals have different states such as capacitive, resistive, symmetrical and unsymmetrical waveforms that classifies the surface condition of the polymeric insulation. Tracking and erosion tests based on BS EN 60587-2007 standard are developed and constructed to capture the set of those leakage current states. Then, the leakage current signals are captured and transfer to personal computer using data acquisition system (DAQ) for monitoring and storing purpose. Graphical User Interface (GUI) is developed using Visual Basic (VB) for the real time analysis of the leakage current for insulator surface condition monitoring system. At the end of this research, the developed system shows that it is appropriate and reliable to implement the leakage current monitoring system for determining the leakage current characteristic of insulating surface condition.